2009
DOI: 10.1115/1.4000435
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxide Magnetic Nanotubes and Their Drug Loading and Release Capabilities

Abstract: Iron oxide magnetic nanomaterials are among the most widely used nanomaterials in nanomedicine. Due to their magnetic and structural properties, iron oxide magnetic nanotubes are extremely attractive for biomedical applications. This paper presents the synthesis of iron oxide magnetic nanotubes, and their potential applications in drug delivery. Three types of iron oxide magnetic nanotubes, i.e., hematite, maghemite, and magnetite, were synthesized using template and hydrothermal methods, and the effects of sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…AIBN initiated polymerization of DMAEMA in presence of MBA in SCC has afforded PDMAEMA with a pair of absorptions at 227 (weak) 245 (strong) nm. Such blue shift in the absorption of PDMAEMA over monomer may be assigned to the loss of the unsaturation of the vinyl functionality as a result of polymerization reaction (Figure 1 (Figure 3a and 3c) [41]. The respective hkl values of FNPs are in close agreement with ASTM data [42].…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…AIBN initiated polymerization of DMAEMA in presence of MBA in SCC has afforded PDMAEMA with a pair of absorptions at 227 (weak) 245 (strong) nm. Such blue shift in the absorption of PDMAEMA over monomer may be assigned to the loss of the unsaturation of the vinyl functionality as a result of polymerization reaction (Figure 1 (Figure 3a and 3c) [41]. The respective hkl values of FNPs are in close agreement with ASTM data [42].…”
Section: Resultssupporting
confidence: 75%
“…The magnetic behavior of materials depends on many factors, such as elemental composition, crystallinity, shape, size and orientation [41]. As the size of the magnetic materials increases, their coercivity and remanence increase accordingly [37].…”
Section: Resultsmentioning
confidence: 99%
“…Several efforts propose the encapsulation of Fe NWs with carbon coatings for different applications such as magnetic nanosensors and magnetic recording media 16–18. The saturation magnetization ( M S ) of pure Fe is superior to that of most soft magnetic materials, while its biocompatible nature is also advantageous 19–21. Therefore, it is an attractive element to be used in magnetic TDD nanodevices.…”
Section: Introductionmentioning
confidence: 99%
“…Recent applications of magnetic NTs have mainly been focused in the biological field. Chen et al (2010Chen et al ( , 2011cChen et al ( , 2012b demonstrated drug loading and releasing capabilities of hematite, maghemite, and magnetite NTs fabricated using a template-assisted method combined with hydrothermal synthesis, as well as their biocompatibility. Magnetic NTs formed by magnetite NPs embedded in silica NTs were reported by Son et al (2005Son et al ( , 2006 as powerful imaging nanostructures for MRI and to track drug delivery controlled by an external magnetic field and hence directed to specific anatomical sites in vivo (Mitchell et al, 2002).…”
Section: Applications Of Magnetic Ntsmentioning
confidence: 99%